Oyster spat recruitment in Espírito Santo State, Brazil, using recycled materials (Brazilian Journal of Oceanography, 2008)
This paper evaluated the effectiveness of four types of oyster spat collectors, made with recycled materials, in the recruitment of the mangrove oyster Crassostrea spp. at five sites in the Benevente river estuary, Anchieta District and on two islands in Piúma District, both in Espírito Santo State. The collectors were made of: 1- oyster shells, 2- PET bottles, 3- car tires and 4- tiles, all of them suspended by ropes and tied to roots of Rhizophora mangle or mussel long-lines. The number of spat recruited on each collector and their shell lengths were registered bimonthly, as well as the physico-chemical-trophic parameters of the water: salinity, temperature, dissolved oxygen, particulate organic matter and chlorophyll a, which were correlated (by Spearman's correlation) with the number of spat recruited. Spat settlement was significantly higher on oyster shell, tile and tire collectors, mainly at points with higher salinities, such as Praia do Coqueiro in Anchieta and on Meio and Cabrito Islands in Piúma (Kruskal-Wallis: H= 10.01; 3 d.f.; p < 0.05). Oyster spat recruitment occurred throughout the year, being higher from November to February, but because of losses due to storms or theft, the difference was not statistically significant (Kruskal-Wallis: H=1.42; 7 d.f.; p >; 0.05). The number of oyster spat was positively correlated with the salinity (ρs= 0.331; p < 0.05) and water temperature (ρs= 0.48; p < 0.05), revealing that areas with higher salinities and summer months were better for spat collection.